Strategi Pembelajaran Untuk Mengatasi Problematika Kemampuan Presentasi Logis Dan Sistematis Pada Siswa Sd - Rina Indrawaty (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
This research aims to overcome students' difficulties in preparing logical and systematic presentations by implementing project-based learning (PJBL) strategies. The problem faced is the limited ability of students to respond and present information effectively. This research used mixed methods, involving observation, interviews with teachers, as well as pretest and posttest tests on 25 grade 5 elementary school students to evaluate the effectiveness of this strategy. Qualitative data was collected through observation and interviews to understand student responses, while quantitative data was obtained from the results of the pretest and posttest which were compared using the paired t test. The research results show that PJBL is effective in improving students' presentation skills logically and systematically, as well as increasing self-confidence and collaboration skills. Based on these results, it is recommended that teachers consider implementing PJBL with a focus on real experience and collaboration to achieve more optimal learning.